From Policy to Practice: Investigating National Social Assistance Schemes in Arunachal Pradesh - Das, Bijay; Sharjo, Pema Dorjee; Phukan, Jinu (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Even though India has made great strides in lowering its poverty rates, a sizable portion of the population still lives in poverty. The poverty rate has declined over time, and in a growing nation like India, the crucial role that social assistance programs and policies play in eradicating poverty is evident. To establish a national policy for social assistance for the needy and eradicating the poverty, the Indian government introduced the National Social Assistance Program (NSAP) on August 15, 1995. The present study mainly focusing on the financial advancement of the IGNOAPS, IGNWPS and IGNDPS in the Arunachal Pradesh. The sources of data used in this study is secondary in nature and collected from the Economics and Statistics department of Arunachal Pradesh. The descriptive statistics has been employed to carry out this study and the results depict that in Arunachal Pradesh under NSAP, some districts have very few beneficiaries. Both central and state government must standfast for providing financial support and assistance to the actual beneficiaries, which can lead to inclusive growth and support social security in the underserved sections of the society.